Activité antimicrobienne des bactéries lactiques isolées à partir du lait de chamelle vis-à-vis des germes impliqués dans les intoxications alimentaires - SADEG, MERIEM (My University, 2020)
Food contamination is a major problem for the consumer, exploiting bacterial interac-tions is a new way to fight against undesirable germs. Several strains were isolated and identified from a sample of raw camel milk from different regions: El -Oued (Algeria), Kerman (Iran), Al-wafra and kabad (Kuwait), to test their antimicrobial activity against pathogenic strains and to select strains with good antimicrobial activity. Strain identification was done by phenotypic and genotypic methods. Genotypic identification was performed by PCR and 16S rRNA sequencing. The isolated strains were tested for antimicrobial effect by the following methods: well diffusion, disc diffusion, agar spot method and spot-on-the-lawn method. Species identification of the isolated lactic strains showed that the isolates are distributed to the species Lactococcus lactis subsp lactis, Lactococcus.lactis subsp cremoris, Lactococcus sp, Pediococcus acidilactici, Pediococcus pentosaceus, Streptococcus ther-mohlus, Streptococcus infantarius, Lactobacillus amylophilus, Lactobacillus plantarum, Weissella confuse et Weissella paramesenteroides, Enterococcus faecium, et Leuconostoc mesenteroides. Results of antimicrobial activity indicate that most strains tested had antibacterial activity against pathogenic strains (gram positive and negative strains). Measurement of the inhibition diameters reveals diameters ranging from1 to 46 mm. Camel milk is a source of strains with antimicrobial activity.
Keywords: Camel milk; Lactic acid bacteria; Pathogenic bacteria; antimicrobial activity.